Movement Patterns of Bali Bull (Bos sondaicus) Sperms After Supplementation of Micronutrients Zn, Selenium, and Vitamin E - Arisanti, N.; Yusuf, M.; Toleng, A. L. (Faculty of Animal Science, Hasanuddin University, Makassar, Indonesia, 2025)
In ruminant livestock, it is very important to pay attention to the adequacy of micro minerals and vitamins, considering that minerals and vitamins are absolute and must be present in the feed so that the health and productivity of the livestock is not disturbed. To produce quality semen, vitamin E, selenium and zinc are needed. These micronutrients play a role in the spermatogenesis process which will have an impact on the quality of spermatozoa produced by male livestock. The aim of this study was to determine the effect of supplementation of micronutrient on sperm movement pattern of Bali bull. This study was used two Bali bull aged 4-5 years with a body weight of 300-350 kg. The study was divided into two periods of treatments and each period was carried out for three weeks. In the first period (control), experimental Bali bull was fed natural grasses and concentrate (1% of body weight). Furthermore, in the second period (treatment period), the feed was similar as the first period with the addition of a mixture of minerals (Zn and Se) and vitamin E. The volume, color, pH, viscosity and movement pattern of the bull's sperm were recorded. Likewise, sperm concentration, motility, viability and abnormality were measured. Fresh semen was diluted with Andromed® accordingly before subsequent processing. Data were analyzed using paired student t-test. The results of the study showed that the macroscopic quality of fresh semen of Bali bull improved after supplementation of micronutrient. The movement pattern of spermatozoa after administration of micronutrient supplements did not have a significant effect (P>0.05). It can be concluded that micronutrient supplementation in Bali bulls can improve macroscopic evaluation, abnormality, viability, concentration and maintained spermatozoa movement patterns. Keywords: Bali bull, spermatozoa, micronutrient, semen quality, and movement